Assessment of Capacity to Consent by Nurses Who Deliver Health Care to Patients Who Misuse Substances. (27th September 2016) - Taylor, Darlene; Ho, Anita; Mâsse, Louise C.; Van Borek, Natasha; Li, Neville; Patterson, Michelle; Ogilvie, Gina; Buxton, Jane A.
This qualitative study explored the current practice that nurses use to assess capacity to consent to health care (CTC-HC) in street outreach settings. Key informant interviews were conducted with a purposive sample of nurses from each of British Columbia's five regional health authorities, allowing nurses to describe their lived experiences with assessing CTC-HC. Content analysis was used to summarize information captured in the data. A total of 19 nurses participated in the study. Five themes emerged from the data: (a) internal guiding forces that contribute to the nurses' assessment, (b) external influences that contribute to the nurses' assessment, (c) measures that are important for assessing CTC-HC, (d) threshold setting, and (e) context (physical and interpersonal) within which assessment of capacity takes place. These elements will be incorporated into a capacity assessment tool that can be used in nursing best practices.